Microbial Degradation of Petroleum Hydrocarbon (Bangladesh Journal of Microbiology, 2011)
The present research was undertaken to isolate and characterize petroleum hydrocarbon degrading microbes from ship-breaking yards at Vatiary and Kumira coast in Chittagong. Twenty different petroleum hydrocarbon contaminated composite samples were collected and the total bacterial count was found to vary between 2.7×103 cfu/ gm and 1.77×107 cfu/ gm. Ten isolates were finally selected through secondary screening by Bushnell-Hass mineral salt medium using kerosene, diesel and engine oil as carbon source. They were provisionally identified and found closely related to the species Listeria monocytogenes, Staphylococcus aureus, Pseudomonas alcaligenes, Listeria grayi, Bacillus pasteurii, Bacillus badius, Bacillus cirroflagellosus, Bacillus circulans, Bacillus brevis and Citrobacter freundii. Greasy spot test was used as the primary indicator of microbial degradation of kerosene, diesel and engine oil. A more specific experiment was carried out to estimate the rate of degradation by the isolates. The highest (96.8%) degradation of diesel was shown by B. brevis, followed by 92%, 88.8% and 84.8% of diesel degradation by the strains of P. alcaligenes, B. cirroflagellosus and C. freundii, respectively. The highest degradation of kerosene (78.26%) and engine oil (43.97%) by S. aureus and L. monocytogenes respectively, were also observed. Keywords: Microbes; Petroleum hydrocarbon; Degradation DOI: http://dx.doi.org/10.3329/bjm.v27i1.9161 BJM 2010; 27(1): 10-13